Changes in the quality of kombucha during fermentation: A study of microbial, physicochemical and sensory attributes - Rahmawati, Lufi Karisma (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Kombucha is a fermented tea beverage known for its health-promoting properties, largely due to its antioxidant-rich polyphenolic compounds. This study aims to examine how fermentation influences the microbial, physicochemical and sensory qualities of kombucha, focusing on microbial growth, polyphenols, total acids, total solids, and sensory attributes. Methods: A literature review approach was employed to synthesize findings from relevant studies on kombucha fermentation and its biochemical mechanisms. Findings: Results show that extended fermentation reduces microbial growth through the antimicrobial activity of phenolic compounds, increases polyphenol and organic acid content via biotransformation. Total solids decline over time due to the conversion of components into volatile metabolites, while acidity, sour aroma, and color brightness intensify with longer fermentation. Conclusion: These findings highlight fermentation duration as a critical factor shaping kombucha’s functional properties and consumer acceptability. Novelty/Originality of this article: The novelty of this article lies in its integrated review of fermentation effects across multiple quality parameters, offering valuable insights for optimizing kombucha as a functional beverage.